The legal basis of the technology of using the Face ID system in personal identification - Doszhanova А.Б.; Begaliyev Е.Н. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2025)
In the current era of globalization and digital transformation, the issue of accurate and reliable personal identification has become a key factor in enhancing public safety and improving the efficiency of law enforcement systems. In this context, biometric technologies - particularly Face ID systems - are widely recognized as innovative tools that enable automated recognition of individuals based on facial features with high speed, accuracy, and reliability. This article provides a comprehensive examination of the technological foundations of Face ID, the use of artificial intelligence and machine learning algorithms, and the practical implementation of this technology in the activities of law enforcement agencies of the Republic of Kazakhstan. Special attention is given to the legal framework, its compliance with international standards for the protection of personal data, and the safeguarding of fundamental human rights and freedoms during the application of biometric systems. The study analyzes the testing and operational use of Face ID technologies within the Ministry of Internal Affairs, the Prosecutor General’s Office, and national security bodies of Kazakhstan. Additionally, a comparative analysis of international experience is conducted, focusing on the practices of the United States, the European Union, China, and Japan in employing facial recognition systems in law enforcement. The article explores legal and technical aspects of international cooperation, including the importance of creating integrated biometric databases and harmonizing technological standards. The research findings substantiate the effectiveness and prospects of using Face ID in the law enforcement sphere. It highlights key ethical and legal challenges, offers specific recommendations for improving national legislation and technical infrastructure, and frames the technology as a crucial component of Kazakhstan’s digital transformation strategy and its efforts to strengthen public security.